Preparation process of high-strength anti-aging composite rubber material
By using carboxyl-containing hyperbranched polyurethane for chemical crosslinking in natural rubber, a stable three-dimensional chemical crosslinking network is formed, which solves the problem of insufficient mechanical properties and thermal aging resistance of natural rubber materials, and significantly improves its tensile strength and thermal resistance.
Patent Information
- Application Number
- CN202510036297.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-25
AI Technical Summary
Natural rubber materials have poor mechanical properties and insufficient heat-resistant aging performance.
Carboxyl-containing hyperbranched polyurethane is used to chemically cross-link natural rubber and epoxidized natural rubber to form a stable three-dimensional chemical cross-linking network, which improves the tensile strength and elongation of break of rubber materials, and enhances its heat resistance.
It significantly improves the tensile strength and elongation of breaking of natural rubber, enhances its heat resistance and heat aging resistance, and ensures that the material remains high after high-temperature thermal aging treatment.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber, in particular to a preparation process of a high-strength and aging-resistant composite rubber material. Background Art
[0002] Natural rubber is a natural polymer material with cis-1,4-polyisoprene as the main component, and is currently the most widely used general-purpose rubber. It is widely used in the fields of daily necessities, medical supplies, transportation, agriculture, forestry, water conservancy, etc. Improving the mechanical properties of natural rubber, heat aging resistance and other properties have important applications. Polyurethane is a polymer with high mechanical strength, high toughness and simple preparation process. It can be used as a toughening agent, fabric finishing agent, elastomer filler, etc., and is widely used in epoxy resin, rubber, fiber fabrics, etc. Patent CN113999519B discloses a polyurethane modified natural rubber and a preparation method thereof. The polyurethane modified natural rubber obtained by using natural rubber, toluene isocyanate tar particles, polyurethane resin, crosslinking agent, etc. as raw materials has good system compatibility, and has good elasticity and elongation while also having better rigidity. The present invention aims to improve the mechanical properties, heat aging resistance and other properties of natural rubber by using hyperbranched polyurethane containing carboxyl groups. Summary of the invention
[0003] The invention solves the problem that the natural rubber material has poor mechanical properties.
[0004] The technical solution of the present invention is: a preparation process of a high-strength and anti-aging composite rubber material: Step S1: nitrogen is introduced into a flask, and dry polycarbonate diol or polycaprolactone diol, isophorone diisocyanate, toluene-2,4-isocyanate or hexamethylene diisocyanate, dibutyltin dilaurate are added, and the mixture is heated to 75-80° C. and reacted for 2.5-3 hours. Then, acetone and N-(2-hydroxypropionic acid)-diethanolamine are added, and the mixture is reacted at 40-45° C. for 1-1.5 hours. The mixture is distilled under reduced pressure and dried to obtain a carboxyl hyperbranched polyurethane.
[0005] Step S2: adding natural rubber and epoxidized natural rubber into an open mill and mixing over a roller, then adding carboxyl hyperbranched polyurethane, triphenylphosphine, zinc oxide, paraffin, stearic acid, antioxidant 4010, adding sulfur, accelerator N-cyclohexyl-2-benzothiazole sulfonamide, accelerator tetramethylthiuram disulfide after mixing, and thinning after mixing; then vulcanizing in a flat vulcanizer at 140-150° C. for 8-14 minutes, discharging, and obtaining a high-strength and anti-aging composite rubber material.
[0006] Preferably, the mass of diisocyanate, dibutyltin dilaurate and N-(2-hydroxypropionic acid)diethanolamine is 19-25%, 0.3-0.5% and 7-11% of the mass of the polyester polyol, respectively.
[0007] Preferably, the masses of the epoxidized natural rubber, the carboxyl hyperbranched polyurethane and the triphenylphosphine are 20-30%, 2-8% and 0.1-0.5% of the mass of the natural rubber, respectively.
[0008] Preferably, the preparation process of N-(2-hydroxypropionic acid)-diethanolamine is as follows: add diethanolamine and 3-chloro-2-hydroxypropionic acid of 124-132% of the mass of diethanolamine to ethanol, heat to 40-55°C, react for 6-10 hours, concentrate under reduced pressure to remove low-boiling substances, and recrystallize the product in ethanol aqueous solution to obtain N-(2-hydroxypropionic acid)-diethanolamine. The reaction formula is as follows:
[0009] The invention has the beneficial effects of using N-(2-hydroxypropionic acid)-based diethanolamine containing three hydroxyl groups as a chain extender to prepare a novel hyperbranched polyurethane containing carboxyl groups. Natural rubber and epoxy natural rubber are used as the matrix of the rubber material, and under the catalytic action of triphenylphosphine, the carboxyl groups of the hyperbranched polyurethane react with the epoxy groups of the epoxy natural rubber, so that the epoxy natural rubber can be used as a compatibilizer, and the compatibility between the hyperbranched polyurethane and the natural rubber is improved. The hyperbranched polyurethane contains a three-dimensional branched molecular chain structure, and undergoes a grafting reaction with the epoxy natural rubber to form a stable three-dimensional chemical cross-linking network in the natural rubber matrix, and the tensile strength and elongation at break of the natural rubber are significantly increased, and the heat resistance and heat aging resistance are changed. After high-temperature heat aging treatment, the rubber material still has very high tensile strength and elongation at break. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described in combination with the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure. It should be noted that the embodiments in the present disclosure and the features in the embodiments can be arbitrarily combined with each other without conflict.
[0011] Example 1 (1) Add 0.5 g of diethanolamine and 0.62 g of 3-chloro-2-hydroxypropionic acid to 8 mL of ethanol, heat to 45 °C, react for 10 h, and concentrate under reduced pressure to remove low-boiling substances. The product is recrystallized in 70% by volume ethanol aqueous solution to obtain N-(2-hydroxypropionic acid)-diethanolamine.
[0012] (2) Nitrogen was introduced into the flask, and 10 g of dry polycaprolactone diol 1000, 2.1 g of toluene-2,4-isocyanate, and 0.044 g of dibutyltin dilaurate were added, and the mixture was heated to 75 °C and reacted for 3 h. Then, 10 mL of acetone and 0.9 g of N-(2-hydroxypropionic acid)diethanolamine were added, and the mixture was reacted at 40 °C for 1.5 h. The mixture was distilled under reduced pressure and dried to obtain carboxyl hyperbranched polyurethane.
[0013] (3) 100 g of natural rubber and epoxidized natural rubber were added to an open mill and mixed over a roller. Then, 2 g of carboxyl hyperbranched polyurethane, 0.1 g of triphenylphosphine, 4 g of zinc oxide, 1.3 g of paraffin wax, 1.7 g of stearic acid, and 0.8 g of antioxidant 4010 were added. After mixing, 1.2 g of sulfur, 1 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.4 g of accelerator tetramethylthiuram disulfide were added. After mixing, the mixture was thinned. Then, the mixture was vulcanized at 150° C. for 10 min in a flat vulcanizer, and the material was discharged to obtain a high-strength and anti-aging composite rubber material.
[0014] Example 2 (1) Add 0.5 g of diethanolamine and 0.66 g of 3-chloro-2-hydroxypropionic acid to 10 mL of ethanol, heat to 40°C, react for 10 h, and concentrate under reduced pressure to remove low-boiling substances. The product is recrystallized in a 70% by volume ethanol aqueous solution to obtain N-(2-hydroxypropionic acid)-diethanolamine.
[0015] (2) Nitrogen was introduced into the flask, and 10 g of dry polycarbonate diol 1000, 2.5 g of isophorone diisocyanate, and 0.05 g of dibutyltin dilaurate were added. The mixture was heated to 80°C and reacted for 2.5 h. Then, 15 mL of acetone and 1.1 g of N-(2-hydroxypropionic acid)diethanolamine were added and reacted at 40°C for 1.5 h. The mixture was distilled under reduced pressure and dried to obtain carboxyl hyperbranched polyurethane.
[0016] (3) 100 g of natural rubber and epoxidized natural rubber were added to an open mill and mixed over a roller. Then, 2 g of carboxyl hyperbranched polyurethane, 0.1 g of triphenylphosphine, 3.5 g of zinc oxide, 1.3 g of paraffin wax, 2.4 g of stearic acid, and 1 g of antioxidant 4010 were added. After mixing, 1.6 g of sulfur, 0.8 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.5 g of accelerator tetramethylthiuram disulfide were added. After mixing, the mixture was thinned. Then, the mixture was vulcanized at 140°C for 14 min in a flat vulcanizer, and the material was discharged to obtain a high-strength and anti-aging composite rubber material.
[0017] Example 3 (1) Add 0.5 g of diethanolamine and 0.62 g of 3-chloro-2-hydroxypropionic acid to 8 mL of ethanol, heat to 55 °C, react for 6 h, and concentrate under reduced pressure to remove low-boiling substances. The product is recrystallized in 70% by volume ethanol aqueous solution to obtain N-(2-hydroxypropionic acid)-diethanolamine.
[0018] (2) Nitrogen was introduced into the flask, and 10 g of dry polycaprolactone diol 1000, 1.9 g of hexamethylene diisocyanate, and 0.03 g of dibutyltin dilaurate were added. The mixture was heated to 75 °C and reacted for 3 h. Then, 15 mL of acetone and 0.7 g of N-(2-hydroxypropionic acid)diethanolamine were added and reacted at 45 °C for 1 h. The mixture was distilled under reduced pressure and dried to obtain carboxyl hyperbranched polyurethane.
[0019] (3) 100 g of natural rubber and epoxidized natural rubber were added to an open mill and mixed over a roller. Then, 2 g of carboxyl hyperbranched polyurethane, 0.1 g of triphenylphosphine, 4 g of zinc oxide, 1 g of paraffin, 2.4 g of stearic acid, and 1 g of antioxidant 4010 were added. After mixing, 1.6 g of sulfur, 1 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.4 g of accelerator tetramethylthiuram disulfide were added. After mixing, the mixture was thinned. Then, the mixture was vulcanized at 150°C for 8 min in a flat vulcanizer, and the material was discharged to obtain a high-strength and anti-aging composite rubber material.
[0020] Example 4 (1) 100 g of natural rubber and epoxidized natural rubber are added to an open mill and mixed over a roller, and then 5 g of carboxyl hyperbranched polyurethane (prepared in Example 1), 0.33 g of triphenylphosphine, 4 g of zinc oxide, 1.3 g of paraffin, 1.7 g of stearic acid, and 0.8 g of antioxidant 4010 are added. After mixing, 1.2 g of sulfur, 1 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.4 g of accelerator tetramethylthiuram disulfide are added. After mixing, the mixture is thinned; then, the mixture is vulcanized at 150° C. for 10 min in a flat vulcanizer, and the material is discharged to obtain a high-strength and anti-aging composite rubber material.
[0021] Example 5 (1) 100 g of natural rubber and epoxidized natural rubber are added to an open mill and mixed over a roller, and then 8 g of carboxyl hyperbranched polyurethane (prepared in Example 1), 0.5 g of triphenylphosphine, 4 g of zinc oxide, 1.3 g of paraffin, 1.7 g of stearic acid, and 0.8 g of antioxidant 4010 are added. After mixing, 1.2 g of sulfur, 1 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.4 g of accelerator tetramethylthiuram disulfide are added. After mixing, the mixture is thinned; then, the mixture is vulcanized at 150° C. for 10 min in a flat vulcanizer, and the material is discharged to obtain a high-strength and anti-aging composite rubber material.
[0022] Comparative Example 1 (1) 100 g of natural rubber and epoxidized natural rubber were added to an open mill and mixed over a roller. Then, 0.1 g of triphenylphosphine, 4 g of zinc oxide, 1.3 g of paraffin wax, 1.7 g of stearic acid, and 0.8 g of antioxidant 4010 were added. After mixing, 1.2 g of sulfur, 1 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.4 g of accelerator tetramethylthiuram disulfide were added. After mixing, the mixture was thinned. Then, the mixture was vulcanized at 150° C. for 10 min in a flat vulcanizer, and the material was discharged to obtain a high-strength and anti-aging composite rubber material.
[0023] Comparative Example 2 (1) Nitrogen was introduced into a flask, and 10 g of dry polycaprolactone diol 1000, 2.1 g of toluene-2,4-isocyanate, and 0.044 g of dibutyltin dilaurate were added. The mixture was heated to 75 °C and reacted for 3 h. Then, 10 mL of acetone and 0.9 g of diethanolamine were added and the mixture was reacted at 40 °C for 1.5 h. The mixture was distilled under reduced pressure and dried to obtain a hyperbranched polyurethane.
[0024] (2) 100 g of natural rubber and epoxidized natural rubber were added to an open mill and mixed over a roller. Then, 2 g of hyperbranched polyurethane, 0.1 g of triphenylphosphine, 4 g of zinc oxide, 1.3 g of paraffin wax, 1.7 g of stearic acid, and 0.8 g of antioxidant 4010 were added. After mixing, 1.2 g of sulfur, 1 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.4 g of accelerator tetramethylthiuram disulfide were added. After mixing, the mixture was thinned. Then, the mixture was vulcanized at 150° C. for 10 min in a flat vulcanizer, and the material was discharged to obtain a high-strength and anti-aging composite rubber material.
[0025] Comparative Example 3 (1) Nitrogen was introduced into a flask, and 10 g of dry polycaprolactone diol 1000, 2.1 g of toluene-2,4-isocyanate, and 0.044 g of dibutyltin dilaurate were added. The mixture was heated to 75°C and reacted for 3 h. Then, 10 mL of acetone and 0.9 g of 2,2-dimethylolpropionic acid were added and reacted at 40°C for 1.5 h. The mixture was distilled under reduced pressure and dried to obtain carboxyl polyurethane.
[0026] (2) 100 g of natural rubber and epoxidized natural rubber were added to an open mill and mixed over a roller. Then, 2 g of carboxyl polyurethane, 0.1 g of triphenylphosphine, 4 g of zinc oxide, 1.3 g of paraffin wax, 1.7 g of stearic acid, and 0.8 g of antioxidant 4010 were added. After mixing, 1.2 g of sulfur, 1 g of accelerator N-cyclohexyl-2-benzothiazole sulfonamide, and 0.4 g of accelerator tetramethylthiuram disulfide were added. After mixing, the mixture was thinned. Then, the mixture was vulcanized at 150°C for 10 min in a flat vulcanizer, and the material was discharged to obtain a high-strength and anti-aging composite rubber material.
[0027] The tensile properties of the composite rubber material are tested according to the method of GB / T 528-2009. The composite rubber material is heat aged at 150°C for 120 hours in a blast dryer, and the tensile properties are tested after cooling.
[0028] Table 1
[0029] Compared with Comparative Example 1, carboxyl-containing hyperbranched polyurethane is added to Examples 1-5. Under the catalytic action of triphenylphosphine, the carboxyl groups of the hyperbranched polyurethane react with the epoxy groups of the epoxy natural rubber, so that the epoxy natural rubber can be used as a compatibilizer, thereby improving the compatibility between the hyperbranched polyurethane and the natural rubber. The hyperbranched polyurethane contains a three-dimensional branched molecular chain structure, and undergoes a grafting reaction with the epoxy natural rubber to form a stable three-dimensional chemical cross-linking network in the natural rubber matrix. The tensile strength and elongation at break of the natural rubber are significantly increased, and the heat resistance and heat aging resistance are changed. After high-temperature heat aging treatment, the rubber material still has very high tensile strength and elongation at break.
[0030] In Comparative Example 2, diethanolamine is used as a chain extender. The obtained hyperbranched polyurethane does not contain a carboxyl group and cannot react with epoxy natural rubber. The hyperbranched polyurethane has poor compatibility and dispersibility in natural rubber materials. The increase in the tensile properties of the rubber material is low, and the tensile strength and elongation at break are lower than those in the embodiments.
[0031] In Comparative Example 3, 2,2-dihydroxymethylpropionic acid is used as a chain extender. The obtained carboxyl polyurethane is a linear molecular chain without a hyperbranched three-dimensional chemical cross-linking network. The toughening effect on natural rubber is poor, the increase in the tensile properties of the rubber material is low, and the tensile strength and elongation at break are lower than those in the embodiments.
Claims
1. A process for preparing a high-strength and anti-aging composite rubber material, characterized in that: The preparation process is: Step S1: nitrogen is introduced into a flask, and dry polyester polyol, diisocyanate, and dibutyltin dilaurate are added, heated to 75-80° C., reacted for 2.5-3 hours, and then acetone and N-(2-hydroxypropionic acid) diethanolamine are added, reacted at 40-45° C. for 1-1.5 hours, and vacuum distilled and dried to obtain a carboxyl hyperbranched polyurethane; Step S2: adding natural rubber and epoxidized natural rubber into an open mill and mixing over a roller, then adding carboxyl hyperbranched polyurethane, triphenylphosphine, zinc oxide, paraffin, stearic acid, antioxidant 4010, adding sulfur, accelerator N-cyclohexyl-2-benzothiazole sulfonamide, accelerator tetramethylthiuram disulfide after mixing, and thinning after mixing; then discharging the material after vulcanization in a flat vulcanizer to obtain a high-strength and anti-aging composite rubber material.
2. The preparation process of the high-strength and anti-aging composite rubber material according to claim 1, characterized in that: The masses of the diisocyanate, dibutyltin dilaurate and N-(2-hydroxypropionic acid)diethanolamine are 19-25%, 0.3-0.5% and 7-11% of the mass of the polyester polyol respectively.
3. The preparation process of the high-strength and anti-aging composite rubber material according to claim 2, characterized in that: The diisocyanate is isophorone diisocyanate, toluene-2,4-isocyanate or hexamethylene diisocyanate.
4. The preparation process of the high-strength and anti-aging composite rubber material according to claim 2, characterized in that: The polyester polyol is polycarbonate diol or polycaprolactone diol.
5. The preparation process of the high-strength and anti-aging composite rubber material according to claim 1, characterized in that: The masses of the epoxidized natural rubber, carboxyl hyperbranched polyurethane and triphenylphosphine are 20-30%, 2-8% and 0.1-0.5% of the mass of the natural rubber respectively.
6. The preparation process of the high-strength and anti-aging composite rubber material according to claim 1, characterized in that: The vulcanization temperature is 140-150° C. and the vulcanization time is 8-14 minutes.
7. The preparation process of the high-strength and anti-aging composite rubber material according to claim 1, characterized in that: The preparation process of N-(2-hydroxypropionic acid)-diethanolamine is as follows: adding diethanolamine and 3-chloro-2-hydroxypropionic acid into ethanol, heating to 40-55° C., reacting for 6-10 hours, concentrating under reduced pressure to remove low-boiling substances, and recrystallizing the product in an ethanol aqueous solution to obtain N-(2-hydroxypropionic acid)-diethanolamine.
8. The process for preparing the high-strength and anti-aging composite rubber material according to claim 7, characterized in that: The mass of the 3-chloro-2-hydroxypropionic acid is 124-132% of the mass of diethanolamine.
Citation Information
Patent Citations
A polyurethane-modified natural rubber and its preparation method
CN113999519B